Adjuvant Pelvic Radiation "Sandwiched" Between Paclitaxel/Carboplatin Chemotherapy in Women With Completely Resected Uterine Serous Carcinoma: Long-term Follow-up of a Prospective Phase 2 Trial. Issue 9 (November 2018) - Frimer, Marina; Miller, Eirwen M.; Shankar, Viswanathan; Girda, Eugenia; Mehta, Keyur; Smith, Harriet O.; Kuo, Dennis Y. S.; Goldberg, Gary L.; Einstein, Mark H.
Abstract : Objective: We prospectively evaluated patients with completely resected uterine serous carcinoma (USC) treated with radiation "sandwiched" between carboplatin/paclitaxel (C/T). The primary objective was to determine the safety profile, and the secondary outcome was to evaluate progression-free and overall survival. Methods: Surgically staged patients with completely resected USC were enrolled to receive 3 cycles of paclitaxel 175 mg/m 2 and carboplatin (area under the curve, 6–7.5) every 21 days, followed by radiotherapy and an additional 3 cycles of T/C at area under the curve of 5–6 (6 cycles + radiotherapy). Toxicity was graded according to National Cancer Institute Common Toxicity Criteria, version 4.03. Kaplan-Meier and log-rank tests were used to compare survival probabilities. Results: One hundred forty patients were enrolled, of which 132 were evaluable, completed at least 3 cycles of chemotherapy and radiation. One hundred seven (81%) completed 6 cycles of chemotherapy and radiation. Patients with early-stage (I/II) disease have survival probabilities of 0.96 and 0.81 at 2 and 5 years. Patients with stage I USC and lymphovascular invasion have considerably worse overall survival, with 2.7 times' higher risk of death than those without lymphovascular invasion. Patients with late-stage (III/IV) disease had overall survival probabilities of 0.64 and 0.18 at 2 and 5 years, which is far higher survival than what has been reported in single-modality trials. Interestingly, and different than what is reported in other studies, there is no difference in survival in African Americans versus whites/other races who were evaluable. Of the 779 cycles administered, 22% and 14% of cycles were associated with grades 3 and 4 hematologic toxicities, respectively. Grades 3 and 4 nonhematologic toxicities occurred in 6.9% of cycles. Conclusions: The long-term follow-up in this study demonstrates that "sandwich" therapy is an efficacious, well-tolerated treatment approach with acceptable toxicities. Lymphovascular invasion (LVSI) is a significantly poor prognostic factor in stage I USC. Multimodal "sandwich" therapy should be considered in all USC patients who have undergone complete surgical resection and staging. Abstract : Supplemental digital content is available in the text.